Child's play [compact disc, unabridged] : a novel - Steel, Danielle (Recorded Books, 2019)
Enduring her late husband's death by embracing strict self-discipline to secure her career and the prospects of her children, a prestigious Manhattan attorney is confronted by astonishing secrets and an out-of-wedlock baby.